Effectiveness and safety of Humalog Mix 50/50 versus Humalog Mix 75/25 in Chinese patients with type 2 diabetes - Zafar MI; Ai X; Shafqat RA; Gao F (Dove Medical Press, 2014)
Mohammad Ishraq Zafar,1,* Xinquan Ai,2,* Raja Adeel Shafqat,3 Feng Gao1  1Department of Endocrinology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 2Zhijiang Petrochemical Hospital, Zhijiang, People’s Republic of China; 3Department of Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China  *These authors contributed equally to this work Abstract: Humalog Mix 75/25 insulin analog is widely used in the People’s Republic of China to treat type 2 diabetes mellitus, but the Humalog Mix 50/50 analog is not as yet widely used or assessed. The purpose of this 12-week, parallel-group, randomized, treat-to-target study was to evaluate the difference in clinical efficacy, safety, and outcome of treatment between Humalog Mix 50/50 and Humalog Mix 75/25 analogs in Chinese patients with type 2 diabetes mellitus. In total, 146 insulin-naïve patients with type 2 diabetes mellitus and aged 18–75 years were randomized and treated twice a day with either Humalog Mix 50/50 (group A) or Humalog Mix 75/25 (group B). We monitored levels of fasting blood glucose, 2-hour postprandial blood glucose, and glycosylated hemoglobin (HbA1c) in patients in both groups prior to and 3 months post treatment, the average time to achieve target blood glucose level, and frequency of hypoglycemic episodes during treatment. We found that group A showed better glycemic control as per fasting blood glucose and 2-hour postprandial blood glucose than group B. Moreover, HbA1c levels in group A (5.5%±1.4%) were lower by 1.0%±0.1% (P<0.05) compared with those in group B (6.5%±1.5%). The time to achieve glucose control was shorter (P<0.05) in group A (12.6±3.6 days) than in group B (22.3±4.7 days). Regarding safety, no significant adverse events or severe hypoglycemia on treatment was observed in either group. Additionally, the 1:1 ratio of Humalog Mix 50/50 showed a trend towards fewer episodes of nocturnal hypoglycemia. Thus, compared with Humalog Mix 75/25, the high-proportion premix insulin analog, Humalog Mix 50/50 showed better glycemic control, achieved target blood glucose levels more rapidly and without an increase in hypoglycemic episodes in Chinese type 2 diabetic individuals and is recommended for use in clinical practice. Keywords: type 2 diabetes mellitus, Chinese type 2 diabetics, Humalog Mix 50/50, Humalog Mix 75/25, premixed insulin lispro 50/50, premixed insulin lispro 75/25